The Internalization of Local Wisdom Value in Dayah Educational Institution - Abdul Hadi (SCAD Independent, 2017)
This research paper investigates: (1) the educational values in local wisdom tradition (2), the internalization strategy of local wisdom values in educational interaction and (3) the implication of the internalization of Acehnese local wisdom in educational interaction in Dayah on students’ behaviour. This qualitative study chose three dayah in Aceh as the sample, they were: Dayah Bustanul Huda (East Aceh), Dayah Mudi Mesra Samalanga (Bireun), and Dayah Darusslam Labuhan Haji (South Aceh). Accordingly, the findings revealed firstly there are three major of educational values in Acehnese local wisdom in Dayah interaction, namely ta’abbudi (worship) value, akhlaqi (moral) value, and the last one is tabarruqi (seek for Allah’s blessing by doing benevolence) value. Secondly, the strategies used in the internalization of local wisdom values are (1) traditional strategy, (2) free strategy, (3) reflective strategy and (4) trans internal strategy. And the last is the implication of those values on the students’ behaviour, those are; sincerity attitude, ta’zim (honor) to teacher, togetherness, modesty, creativity, tolerance, self-reliance, discipline and mutual respect.